(untitled) (Medical Forum Monthly, 2020)
Objective: To find the etiological profile of pancytopenia in children visiting Qazi Hussain Ahmad Medical Complex Nowshera. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Pediatrics, Qazi Hussain Ahmad Medical Complex, Nowshera from January to December 2019. Materials and Methods: Total 119 patients were included in the research. After applying inclusion and exclusion criteria, blood samples were tested in the hospital laboratory. Bone marrow biopsy was done in selected patients according to provisional diagnosis. Data was analysedusing SPSS version 21. Results: Total 119 (55%male and 45%female) patients with mean age6 years + 15.84were recruited. 2% patients had malaria, 8% patients had enteric fever, 15% patient’s leishmaniasis, 50% megaloblastic anemia, 10% aplastic anemia, and 15% of patients had leukemia. Conclusion: Pancytopenia is a common problem in both settings, clinical and hematological practice. Many other comorbidities also present in patients with pancytopenia. It is imperative to recognize the most common etiologies of pancytopenia among patients belong tolocal community because few are entirelytreatable while in others morbidity is reduced and survival is prolonged.